Oriented Microtexturing on the Surface of High-Speed Steel Cutting Tool; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Podgornykh O. A. Oleg Anatolievich; Shamarin N. N. Nikolay Nikolaevich; Filippova E. O. Ekaterina Olegovna (2016, 2016)
Title screen